Experimental investigations of reinforced concrete beams repaired/reinforced by TRC composites. (15th May 2017) - Truong, B.T.; Bui, T.T.; Limam, A.; Si Larbi, A.; Le Nguyen, K.; Michel, M.
Abstract: Reinforcement and repair of reinforced concrete structures is often more economical and sustainable (less cement consumption, less CO2 production) than reconstruction. Currently, the solution of reinforcement/repair by carbon-epoxy materials applied to outer surfaces of the structures is routinely used. However, these composites have limitations in terms of cost, fire resistance and sustainable development criteria. The textile reinforced concrete (TRC) mineral-based composite is envisaged as an alternative solution that can solve, at least partially, the above drawbacks. This work aims to experimentally assess contributions of the strengthening/repair of slender reinforced concrete beams subjected to bending by applying the TRC composite. In the first approach, the use of TRC composites in the case of the repair/strengthening of tank shells will be evaluated on the basis of slender beams. Twelve reinforced concrete "beams" are tested for quasi-static monotonic loading by bending tests over four points among 10 beams that have been reinforced/repaired by composite materials. Several parameters including two different modes of curing conditions (28 days immersion in water at 20 °C; 28 days left in air at 20 °C, 50 RH), and two different types of configurations of the beams (with and without pre-cracking) have been considered. This study highlights the mechanical performance of TRC in strengthening/repair of the reinforced concrete beams by analysing the changes in global behaviour (e.g., load/deflection, failure mode, flexural rigidity) and local behaviour (e.g., deformation of steel, pattern cracking, the crack opening). Further evaluation of the local behaviour of TRC should be conducted to address the damage mechanism by multi-cracking of the material and changing the opening of the crack located on the face of the composite.